Avaliação da dinâmica de impressora 3D com tecnologia fused filament fabrication (FFF): uma investigação baseada em testes de vibração - Corradini, Vitor (Universidade Federal de São Carlos, 2025)
This work investigated the influence of mechanical vibrations in the FFF (Fused Filament Fabrication) 3D printing process by comparing the operating frequencies and resonance frequencies of the main structural components of a 3D printer. Spectral analysis, based on the Fast Fourier Transform (FFT), was applied to data obtained from both impact tests and recordings made during the printing of test specimens with different operational parameters. The adopted methodology involved the systematic variation of print speed, infill density, and infill pattern, totaling 27 experimental combinations. Additionally, accelerometers were used to record the dynamic response in three main regions of the printer: print bed, extruder head, and vertical structure. The obtained data were processed in a MATLAB environment, allowing for direct comparison between the resonance and operational frequency ranges. The results from the impact tests showed specific resonance peaks for each machine component, highlighting the importance of selecting the hammer tip material for signal quality. In the operational analysis, it was observed that the highest vibration amplitudes occurred during calibration, nozzle cleaning, and the printing of the first layer. Furthermore, even with operating frequencies approaching resonance frequencies, the printer functioned without issues. The RMS value analysis identified test specimen number 8 (50 mm/s, 20\% infill density, and gyroid infill pattern) as having the highest vibration levels in the extruder head and print bed, although without causing any damage to the machine. This study fills a gap in the literature by directly correlating printing parameters with the vibrational behavior of a commercial 3D printer, providing valuable insights for process optimization and part quality.
Evaluation of the dynamics of a 3D printer with fused filament fabrication (FFF) technology: an investigation based on vibration tests
Keywords: Impressão 3D; Vibração mecânica; FFT; Frequência natural; FFF; ENGENHARIAS::ENGENHARIA MECANICA::PROCESSOS DE FABRICACAO